RADIKALISASI PETANI MUSLIM DALAM PERSPEKTIF SOSIOLOGIS - Mawardi J, M. (Universitas Islam Negeri Raden Intan Lampung, 2015)
The emergence of the Peasant radicalism is not caused by any defect in the social structure, but because the process of exploitation and domination of one class against another. The Peasant radicalism is understood as a reaction of the proletariat against the bourgeoisie, is an expression of a contradictory class structure. The Socio- economic deprivation and the political repression of the state and economic power market / capitalism is a factor that grows and develops exclusivism resistance. Moreover when there are agrarian policies that harm the interests of the farmers, both in accessing and in the mastery of agrarian resources (land), will give birth to an increasingly harsh peasant resistance, militant, emotional and destructive. The radicalism done by farmers Muslim community, makes the religion fanaticism as a movement ideology and an inspiration source as well as the value used in constructing communalism, even they are able to construct radicalism using religious symbols as edging actions taken thus further motivate and mobilize the resistance. Nevertheless resistance farmers led by warsidi failures, even appearing new stigma as the movement of security meddler who want to establish an Islamic state.